Fixed Point Results for Generalized α,ψ-Contraction Mapping in Rectangular b-Metric Spaces - Mustefa Abduletif Mamud; Kidane Koyas Tola (Abstract and Applied Analysis)
In this paper, we introduce generalized α,ψ-contraction mappings in the setting of rectangular b-metric spaces and established existence and uniqueness of fixed points for the mappings introduced. Our results extend and generalize related fixed point results in the existing literature. We derive some consequences and corollaries from our obtained results. Also, we provide examples in support of our main findings. Furthermore, we determined a solution to an integral equation by applying our obtained results.